DEPICTION OF ISLAM’S COLLAPSES IN ANDALUSIA FROM THE NOVEL SANGKAKALA DI LANGIT ANDALUSIA - Misbahus Surur; Ummi Hasanah; M. Anwar Masadi; Aulia Fadhila Wirmansyah (Journal of Arabic Literature (JaLi), 2023)
This study aims to describe the historical picture of Islam’s collapse  during the Andalusian period in novel "Sangkakala di Langit Andalusia" by Hanum Salsabiela Rais and Rangga Almahendra. This study uses a qualitative approach with a descriptive method using a New Historicism critical approach. The data analysis technique used by the researcher is categorization, tabulation, data analysis and data inference steps. The analysis was carried out by comparing the historical picture in the novel "Sangkakala di Langit Andalusia" with history in history books related to the glory of Islam in Spain such as; “History of the Arabs”; “Penghancuran Buku dari Masa ke Masa”; dan “Bangkit dan Runtuhnya Andalusia”. The results of this study indicate that there is a historical form of Islam’s during the Andalusian period in the plot of novel "Sangkakala di Langit Andalusia", which starts from the emergence of disunity of the Muslim until the collapse of the Islamic sultanate In Andalusia. The presentation of the content’s relevance in the novel and historical facts in this study is divided into three discussions; (1) An emergence of divisions in the Muslims, (2) the fall of the Islamic region to the power of the Christian kingdom, and (3) An Apocalypse in Andalusia.